The Meaning of Self-Reward: A Phenomenological Exploration of Consumer Experiences in Everyday Consumption - Nurul Haeriyah Ridwan; Asriyani Amrullah; Andi Reski Nurhikmah (Universitas Sulawesi Barat, 2026)
The contemporary consumption landscape has shifted from merely fulfilling functional needs to symbolic and emotional experiences, within which the self-reward phenomenon has become a prominent practice. However, existing literature remains largely dominated by quantitative approaches that focus on behavioral antecedents, thereby providing a limited exploration of how consumers assign meaning to their lived experiences regarding self-reward. This research aims to explore the meaning of self-reward through the lens of consumer lived experiences in everyday consumption. This research involved eight informants in Makassar City, Indonesia, selected through purposive sampling. Data were collected through semi-structured in-depth interviews, non-participant observations, and relevant documentation. Data analysis reveals that self-reward is not merely a materialistic purchasing act but a multidimensional experiential practice. The findings identify key emerging dimensions, namely: Self-Appreciation, Emotional Restoration, Personal Achievement, Identity Affirmation, and Psychological Well-Being. Consumers construct the meaning of self-reward as an intrapersonal symbolic dialogue and a coping mechanism to restore emotional balance and negotiate identity amid the demands of modern life. This study contributes to consumer behavior literature by revealing that self-reward is constructed as an intrapersonal symbolic dialogue grounded in perceived deservingness and conscious reflection, through which consumers transform everyday consumption into a meaningful process of emotional restoration, identity affirmation, and psychological well-being. These findings provide practical implications for marketers to design ethical and meaningful consumption experiences that emphasize personal achievement rather than mere product acquisition